THE JUNIOR ACCOUNTANT: HIS PROBLEMS, RESPONSIBILITIES, AND TRAINING. - Scovill, H. T. (The Accounting Review, 1938)
Abstract Pricing of inventory is very often a part of the junior's work along with additions and extensions of inventory. He should obtain specific instructions as to the type of items to be taken off the inventory for the price test. After having set these items down, he should obtain the senior's approval on the extent of his test. The junior should be certain that he has seen all policies that have been charged either to the prepaid-insurance account or to the insurance-expense account. And he must be sure that all policies have actually been charged into one of these accounts. A junior accountant should recognize that his problems, responsibilities and training should make him the best possible type of accountant to serve his organization, clients and society. A sound education in accounting theory, auditing procedure, economics, principles of internal control, law, taxation, and other related subjects. Ability to express ideas and facts in clear, concise and understandable language. Studiousness and perseverance; a real desire to keep up with latest developments in accounting subjects and ever-changing tax laws, and an unwillingness to finish a job or draw a conclusion until he is sure he is right.